Efektivitas Konseling Self Management dalam Mereduksi Problematic Smartphone Use - Arif Setiawan; Dwi Yuwono Puji Sugiharto; Edy Purwanto (Kuras Institute, 2022)
The purpose of the study was to test the effectiveness of self management counseling in reducing students' problematic smartphone use. A quantitative experimental method with a pretest posttest design using repeated actions is applied in this study. There are 6 students who perform as test subject, which was taken from their characteristic of highest problematic smartphone use that analyzed by using mixed ancova repeated measures. The instrument is Problematic Smartphone Use Scale (PSUS) (Kwon et al., 2013). Self management Counseling is conducted in 7 sessions for each counselee in the form of individual counseling. The results showed the average T1 value of 56,17 (SD = 3,37) which then arrived at the T4 measurement obtained with an average of 42,50 (SD = 32,27). As in general, the self management counseling is effective in reducing students' problematic smartphone use. Based on the results of this study, a self management approach can be recommended for guidance and counseling teachers to be able to apply this method as an effort to reduce students' problematic smartphone use at school.